Determinants of occupational choices: A Multinomial logit analysis of selected vavuniya campus graduands in Sri lanka - Thayaparan, A.; Gunathilaka, G.Y.N. (University of Jaffna, 2018)
This study uses multinomial logit model to estimate the impact of significant factors influencing occupational choices among the undergraduates in Sri Lanka. For this purpose, 123 Bachelor of Business Management undergraduates from third and fourth years of the Vavuniya Campus of the University of Jaffna were selected. The primary data were collected through the structured questionnaires and this study predominantly employed multinomial logistic regression model and marginal effects to arrive the findings. Since the discrete choices have more than two categories in the dependent variable, multinomial logit model is more appropriate than other logit or probit models. Job choice was considered as an outcome variable which has six categories whereas salaries, other benefits, working environment, job security, career development and employer reputation were utilized as predictors in the study. Empirical results of the model indicate that all the above variables are important factors that determine the job choices, but their magnitude and significant levels vary across different types of job choices. Salary was considered as an important factor in all job categories except in choice of own business. The respondents who prefer to start their own businesses were more concerned on other benefits while the respondents who prefer to become as an accountant more concerned on career development than other job choices. The major findings of the study may assist the students of Vavuniya Campus in selecting their specialization preferences on the subjects and the academics to improve their curriculum design in the future.
Keywords: Occupational choices; Bachelor of business management undergraduates; Probability of job preferences; Multinomial logit model; Marginal effects